De introductie van het Hollands classicisme in Zweden, aan de hand van twee woonhuizen van de familie De Geer (Bulletin KNOB, 1999)
When the architects Jacob van Campen, Pieter Post and Philips Vingboons introduced classicism in the Dutch Republic in the thirties and forties of the seventeenth century, this architectural principle soon got anchored in the world of commissioners, architects and dilettantes. But it did not remain restricted to the latter group; due to merchants' and architects' frequent travels, Dutch classicism developed into an international design principle.In the course of the seventeenth century various Dutch architects worked abroad or in their own studios at assignments commissioned from abroad. Besides, many a foreign architect travelled to the Dutch Republic in order to follow an education. The distribution of architecture treatises also increased the scope of Dutch classicism.The Dutch Republic proves to have played a more active role in early modern Europe than is suggested in current architecture historiography. The Dutch Republic was not just the recipient of new architecture trends from Italy and France, but also functioned as a centre from where these trends emanated towards North-East Europe in the period 1640-1700.The contacts between the Dutch Republic and Sweden represent a special chapter in the history of architecture of North- East Europe. Two private houses, belonging to the Dutch ironmongers Louis de Geer and his son Louis de Geer jr. play an important part in the introduction of Dutch classicism in Sweden.Fitting in with the traditions of his time, Louis de Geer occupied himself with horticulture and architecture besides his iron and copper trade. His private house, dating from 1646, was the first Dutch classicist building in Stockholm. An analysis of the drawing of the facade, detail drawings and ground plans, point in the direction of a dilettante-architect with the background of a craftsman. And not of a painter, unlike most 17th century architects.Possibly Louis de Geer asked Joost Henne, a Dutch mason in his employment during the building period, to make a design for his house with the aid of sample drawings. At the end of the Thirty Years' War building activity quickly increased in Stockholm; many members of the Swedish nobility followed De Geer's example. However, the 'Riddarhus' is the most extravert example of all Dutch classicist buildings in Stockholm.The facades were designed by Justus Vingboons. In 1668 Louis de Geer's son Louis de Geer jr. commissioned an architect to design a country estate near his copper mill in Finsprong. The notes and watermarks on ground-plan and elevation drawings point to a Dutch architect.A recently unknown series of drawings in the National Museum in Stockholm and an already known series of drawings show strong similarity with the method of the architect Adriaan Dortsman as far as drawing technique, measurements and scale are concerned. Besides, a number of style components in Finsprong are also to be found in other works by Dortsman, such as the Walloon Orphanage, country estate Gunterstein, the Round Lutheran church and the private house Amstel 216.The intensive contact between the Netherlands and Sweden in the seventeenth century primarily consisted of trade contacts, but they also resulted in contacts in the field of culture. Ordering drawings from Dutch architects both by Dutchmen and by Swedes occupied an important place in this respect.Louis de Geer's private house in Stockholm introduced Dutch classicism in Sweden and also stimulated contacts with Dutch architects. Examples are the Riddarhus of Justus Vingboons. The country estate Finsprong was a recently unknown example of Dutch classicism in Sweden. The commissioning of the country estate Finsprong to Adriaan Dortsman signifies a supplement to Dortsman's oeuvre and Dutch and Swedish history of architecture.